Engineered MSW landfills as a future material resource and a sink for long-term storage of organic carbon. Issue 1 (October 2020) - Bramryd, Torleif; Johansson, Michael
Abstract: A controlled, highly engineered landfill has many similarities to natural peatlands or other natural anoxic sediment deposits. In anaerobic MSW landfills, generally about 30-50 percent of the total carbon content in the waste can be converted into biogas and be collected as resource for energy or chemical industry. Remaining long-lived organic carbon, e.g. from lignin remains un-degraded, Organic carbon in fossil derived hydrocarbons, like plastics, will remain rather unaffected in the landfill. In a future with less remaining oil resources, landfill mining of these polymers can be valuable, making the landfill to a future "resource bank". New reactor cell landfill technologies have shown that up to over 90 % of the produced biogas can be collected and used. Approximately 150-250 m 3 of biogas per tonne waste can be extracted from a landfill reactor-cell over a 10-year period. Sequestration of a long-lived organic fraction in a landfill, with an annual input of 100 000 tons of waste, can compensate for annual CO2 emissions from about 20 000 to 25 000 cars. If more than about 60 % of produced biogas can be collected from the landfill, it has positive net effects on climate change. If the waste instead would have been incinerated this would lead to major emissions of fossil CO2, as about 30-50 % of the CO2 in the stack gasses from a waste incinerator has fossil origin.